Osseous associated cervical spondylomyelopathy at the C2‐C3 articular facet joint in 11 dogs. (21st November 2015) - Cooper, C.; Gutierrez‐Quintana, R.; Penderis, J.; Gonçalves, R.
Abstract : In dogs, vertebral canal stenosis at C2‐C3 due to articular facet joint degeneration is only sporadically identified. The authors' aims were to review the clinical presentation, MRI characteristics, treatment and outcome of dogs presenting with this condition. Eleven cases were eligible for inclusion. Neurological examination revealed tetraparesis and proprioceptive ataxia in all 4 limbs in 3/11, proprioceptive tetra‐ataxia only in 4/11, pelvic limb proprioceptive ataxia in 2/11 and no gait abnormalities in 2/11 dogs. Cervical hyperaesthesia was present in 7/11 dogs. MRI revealed bilateral articular facet joint degeneration in 10/11 cases and unilateral degeneration in one. Surgery was performed in six cases and medical management elected in five. Long‐term follow‐up information was available for 11 animals. Four of the surgical cases are alive and have no neurological deficits, one was euthanased for an unrelated condition and one lost to follow‐up. Of the cases managed medically, three are alive showing no neurological deficits, one is alive still displaying neurological deficits and one euthanased for an unrelated condition whilst still ataxic. This study shows that both medical and surgical management can result in good outcomes in dogs with vertebral canal stenosis resulting from articular facet joint degeneration at the level of C2‐C3.